Duck and cover civil defense images in film and television from the Cold War to 9/11 - Matthews, Melvin E. (McFarland & Co., 2012)
"This volume explores how American popular culture has portrayed civil defense from mid-twentieth-century to the immediate post-September 11 era. Analyzes everything from early government propaganda films and 1950s science fiction films to Happy Days, the Reagan-era TV movie The Day After, and the small-screen nostalgia trend after 9/11"--Provided by publisher.